2013
DOI: 10.1590/s1517-83822013000300035
|View full text |Cite
|
Sign up to set email alerts
|

First record of Borrelia burgdorferi B31 strain in Dermacentor nitens ticks in the northern region of Parana (Brazil)

Abstract: The aim of this study was to investigate the presence of DNA of Borrelia burgdorferi sensu lato (s.l.) in ticks that feed on horses used for animal traction in rural Jataizinho, Parana, Brazil. Between February and June 2008, a total of 224 ticks was collected of which 75% were identified as Dermacentor nitens and 25% as Amblyomma cajenense. To amplify B. burgdorferi s.l. DNA, the intergenic space region (ISR) between the 5S (rrf) 23S (rrl) rRNA genes was used as targets for nested-PCR. Two ticks of the D. nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…The presence of ticks in all dogs of this study reinforces the risk of transmission of Brazilian Lyme-Like disease or Baggio-Yoshinari Syndrome agents to humans in the studied area. Furthermore, Gonçalves et al (2013b) detected B. burgdorferi s.l. DNA in ticks of Dermacentor nitens specie in the northern region of the Parana state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of ticks in all dogs of this study reinforces the risk of transmission of Brazilian Lyme-Like disease or Baggio-Yoshinari Syndrome agents to humans in the studied area. Furthermore, Gonçalves et al (2013b) detected B. burgdorferi s.l. DNA in ticks of Dermacentor nitens specie in the northern region of the Parana state.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, some studies have indicated the presence of B. burgdorferi s.l. in ticks from other genera such as Amblyomma, Rhipicephalus and Dermacentor (GONÇALVES et al, 2013b;MANTOVANI et al, 2012;YOSHINARI et al, 2010). Among these vectors, ticks belonging to Ixodes genus seem to be involved in the sylvatic transmission cycle of disease, whereas ticks from Amblyomma genus are associated to transmission between domestic animals and humans (ABEL et al, 2000;SOARES et al, 2000;YOSHINARI et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In order to introduce a Borrelia vaccine to LATAM, there would need to be robust research studies into whether the pathogen exists in this region, whether there are competent tick vectors and wildlife reservoirs, and whether dogs and cats could become infected and go on to develop clinical signs of disease. In Brazil, studies have identified borreliosis in human patients with Brazilian Lyme-like disease or Baggio-Yoshinari syndrome (Yoshinari et al 2003, Mantovani et al 2012, and Borrelia burgdorferi sensu lato in asymptomatic humans (Gonçalves et al 2015) and ticks from the genus Dermacentor (Gonçalves et al 2013) [EB1]. Few reports relate to companion animals, and although anti-Borrelia antibodies have been found in dogs, to our knowledge the pathogen has not been isolated from sick dogs (Spolidorio et al 2010, Nascimento et al 2016 [EB1].…”
Section: Why Do We Not Have a Borrelia Vaccine In Our Country?mentioning
confidence: 99%
“…Estudos soro epidemiológicos de Borrelia spp. foram realizados em várias regiões do Brasil, e em várias espécies hospedeiras, como: bovinos, cães, equinos e animais silvestres e apresentaram valores próximos aos reportados em áreas endêmicas na América do Norte (YOSHINARI et al, 1995;ISHIKAWA et al,1997ISHIKAWA et al, , 2000SOARES et al, 1999;SALLES et al, 2002;MADUREIRA, 2007 (YPARRAGUIRRE et al, 2007;REZENDE et al, 2008) e Dermacentor nitens (GONÇALVES et al, 2013).…”
Section: Relato Do Casounclassified